2015
DOI: 10.1523/jneurosci.5232-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Coinciding Decreases in Discharge Rate Suggest That Spontaneous Pauses in Firing of External Pallidum Neurons Are Network Driven

Abstract: The external segment of the globus pallidus (GPe) is one of the core nuclei of the basal ganglia, playing a major role in normal control of behavior and in the pathophysiology of basal ganglia-related disorders such as Parkinson's disease. In vivo, most neurons in the GPe are characterized by high firing rates (50 -100 spikes/s), interspersed with long periods (ϳ0.6 s) of complete silence, which are termed GPe pauses. Previous physiological studies of single and pairs of GPe neurons have failed to fully disclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…On the other hand, previous pairwise correlation of simultaneously recorded GPe neurons failed to find pause‐to‐pause and pause‐to‐spike correlations, suggesting an intrinsic phenomenon (Elias et al ., ). These conflicting results may be explained by a recent study of our group (Schechtman et al ., ) that employed population analysis, which is more sensitive than pairwise correlation analysis. This population analysis revealed a small (1–2 spikes/s) decrease in the GPe discharge rate coincident with GPe pauses, suggesting that pauses reflect the interplay between common network inhibition and intrinsic cellular properties of GPe neurons.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous pairwise correlation of simultaneously recorded GPe neurons failed to find pause‐to‐pause and pause‐to‐spike correlations, suggesting an intrinsic phenomenon (Elias et al ., ). These conflicting results may be explained by a recent study of our group (Schechtman et al ., ) that employed population analysis, which is more sensitive than pairwise correlation analysis. This population analysis revealed a small (1–2 spikes/s) decrease in the GPe discharge rate coincident with GPe pauses, suggesting that pauses reflect the interplay between common network inhibition and intrinsic cellular properties of GPe neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Such an anatomical organization allows dStr axons to contact the dendrites of multiple GPe neurons. The sharing of dStr inputs by multiple GPe neurons provides an anatomical substrate for synchrony and pause‐burst firing pattern in a large population of GPe neurons, as demonstrated by both experimental and computational studies (Terman et al ., ; Elias et al ., ; Zold et al ., ,b; Kita & Kita, ,b; Adler et al ., ; Schwab et al ., ; Wilson, ; Schechtman et al ., ). As PD progresses, the activity of GPe neurons transitions from decorrelated, single‐spike pacemaking to synchronous, rhythmic bursting (but see Mallet et al ., ).…”
Section: Synaptic and Neuromodulatory Control Of The Gpementioning
confidence: 99%
“…Interestingly, in humans, ethanol appears to decrease GPe activity, as evidenced by neuroimaging studies in which an oral dose of ethanol dampened the increase of GPe activity during a visual task and induced a slight decrease of GPe activity ( Nikolaou et al , 2013 ). Although we are aware that GPe high-frequency neurons are characterized by interspersed pauses in monkeys ( DeLong, 1971 ; Elias et al , 2007 ; Noblejas et al , 2015 ; Schechtman et al , 2015 ), we observed only occasional pausing behavior in some GPe neurons (data not shown). One reason for this difference may be species, as in rodents it has been reported that a subset of high-frequency neurons showed only occasional brief pauses ( Dodson et al , 2015 ; Mallet et al , 2016 ).…”
Section: Discussionmentioning
confidence: 64%